Antimicrobial, Antioxidant, and Cytotoxic Properties of Vasicine Acetate Synthesized from Vasicine Isolated from Adhatoda vasica L. (14th January 2015) - Duraipandiyan, V.; Al-Dhabi, N. A.; Balachandran, C.; Ignacimuthu, S.; Sankar, C.; Balakrishna, K.
Abstract : Adhatoda vasica (L.) (Acanthaceae) is used in the indigenous system of medicine in India. The alkaloid Vasicine was isolated from ethanolic extract of the leaves of A. vasica using column chromatography. Vasicine acetate was obtained by acetylation of Vasicine. Vasicine acetate exhibited good zone of inhibition against bacteria: 10 mm against E. aerogenes, 10 mm against S. epidermidis, and 10 mm against P. aeruginosa . Vasicine acetate showed minimum inhibitory concentration values against bacteria: M. luteus (125  μ g/mL), E. aerogenes (125  μ g/mL), S. epidermidis (125  μ g/mL), and P. aeruginosa (125  μ g/mL). The radical scavenging activity of Vasicine acetate was the maximum at 1000  μ g/mL (66.15%). The compound showed prominent cytotoxic activity in vitro against A549 lung adenocarcinoma cancer cell line. Quantification of Vasicine and Vasicine acetate by HPLC-DAD analysis showed their contents to be 0.2293% and 0.0156%, respectively, on dry weight basis of the leaves. Vasicine acetate could be probed further in drug discovery programme.